"Ngadéngékeun nu mantun"; Constructing the "carita pantun" performance in rice planting ritual of the Baduy indigenous community - Saparudin, Endin; Limbong, Priscila Fitriasih; Setyani, Turita Indah; Permana, R. Cecep Eka (Wacana, Journal of the Humanities of Indonesia, 2025)
This study aims to examine carita pantun performances in ritual contexts as observed in the Baduy community in Kanekes Village, Banten, on several occasions between 2021 and 2023. Carita pantun serves as traditional epics narrated in oral tradition performances accompanied by kacapi musical instruments. Historically, carita pantun was fully integrated into the ritual calendar and performed regularly in various regions in Tatar Sunda including West Java and Banten. Over time, it has been increasingly narrated for secular entertainment. This study explores carita pantun performances that retain a sacred function and remain deeply integrated into the life of the Baduy community. By identifying the distinctive characteristics and observing the roles of speakers and listeners, the analysis emphasizes the importance of the oral text being highly dependent on the context of the specific ritual. The analysis further enriches the understanding of the nature and structure of the carita pantun performances as a traditional ritual in West Java and Banten.